2017
DOI: 10.1136/bmjdrc-2017-000390
|View full text |Cite
|
Sign up to set email alerts
|

Improving the transition from pediatric to adult diabetes care: the pediatric care provider's perspective in Quebec, Canada

Abstract: ObjectivesThe transition from pediatric to adult care is a high-risk period for the emerging adult with diabetes. We aimed to determine adequacy of pediatric transition care structures and explore the pediatric diabetes care provider’s perceptions of transition care.Research design and methodsIn-depth interviews with pediatric diabetes care providers from 12 diabetes centers in Quebec were conducted. We queried alignment with Got Transition’s six core elements of healthcare transition, experiences, and barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 33 publications
(31 reference statements)
1
32
0
2
Order By: Relevance
“…Similarly, research with AYAs with diabetes reported that HCPS’ use of shock tactics about potential morbidity was unhelpful (Garvey et al, ). Nakhla, Bell, Wafa, and Dasgupta () noted that sometimes adult HCPs wrongly expect YAs to be fully autonomous at 18 years and lack understanding of the challenges that are encountered on transfer. The content and quality of patient–provider communication is an essential aspect of developmentally appropriate care that strongly influences adolescents’ transition readiness (van Staa et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, research with AYAs with diabetes reported that HCPS’ use of shock tactics about potential morbidity was unhelpful (Garvey et al, ). Nakhla, Bell, Wafa, and Dasgupta () noted that sometimes adult HCPs wrongly expect YAs to be fully autonomous at 18 years and lack understanding of the challenges that are encountered on transfer. The content and quality of patient–provider communication is an essential aspect of developmentally appropriate care that strongly influences adolescents’ transition readiness (van Staa et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, pediatricians are not familiar with the needs and challenges of young adults and the adult providers are trained with a different perspective of diabetes management strategies and have dissimilar expectations. Furthermore, the psychosocial environment and expectations differ significantly in the two scenarios, and pediatric and adult providers have different perceptions of the transition process (7,8). In pediatrics, the adolescent and young adult with T1DM receive more support, accountability and supervision by the parents and/or guardian in the home environment as well as from the diabetes management team than what is provided in the adult medical system.…”
Section: Review Articlementioning
confidence: 99%
“…4,5,6 Egy kanadai tanulmány öszszegezte az átadás nehézségeit, hiányosságait. 7 Egy átadási ellenőrző lista segíthet, amely az átadással kapcsolatos teendők tervszerű, egymásra épülő folyamatát foglalja össze, lehetőséget ad az…”
Section: Az áTadási Folyamatunclassified